EFFECT OF SEED-BORNE MYCOFLORA ON QUANTITY AND QUALITY OF MUSTARD OIL - AND R. K. BANSAL, A. SHIVPURI, B. S. SIRADHANA (Indian Phytopathology, 2002)
Eighty two seed samples of mustard were collected from nine agro-c1imatic zones of Rajasthan and 16 species of fungi were isolated from these samples. Effect of these fungi were studied on the quantity and quality of mustard oil. Three fungi reduced, six increased and rest did not effect oil content. All the fungal species inflicted unpleasent odour in oil and changed the colour of oil significantly.